History and current status of haymeadows along the stream Kerca: a case study for the scientific foundation of nature conservation treatments: Esettanulmány természetvédelmi célú kezelések megalapozásához - Tóth, Zoltán (JOURNAL OF LANDSCAPE ECOLOGY, 2004)
Traditionally managed haymeadows once were common in the valley of the stream Kerca (south of the village Kercaszomor, Belső-Őrség region, Western Hungary). By today most of these had been replaced by a mosaic of grassland, shrub and forest patches as a result of secondary forest succession. This work calls the attention that the assessment of the current state of (semi)natural habitats is not sufficient in itself for the planning of nature conservation maintenance treatments, but an adequate understanding of vegetation history and previous land use patterns are also necessary. Almost without exception haymeadows in this region are of secondary origin that have been maintained through extensive land use by locals. A chronological sequence of land use forms in the past 100–150 years that may be responsible for the current status of the vegetation should always be considered in addition to the precise appraisal of the present state of plant cover. On the example of haymeadows along the stream Kerca I show how past events may influence the current and future states of vegetation. Awareness of these is inevitable for the proper, site-specific planning and implementation of nature management treatments for conservation. Furthermore, routine habitat maintenance treatments should be accompanied by controlled experimentation on different sorts of treatments in order to achieve a scientifically based management and restoration.
Keywords: landscape history; traditional hay-making agriculture; habitat maintenance; nature conservation